Asthma in Children and Adults—What Are the Differences and What Can They Tell us About Asthma? - Trivedi, Michelle; Denton, Eve (Frontiers in Pediatrics, 2019)
Asthma varies considerably across the life course. Childhood asthma is known for its overall high prevalence with a male predominance prior to puberty, common remission and rare mortality. Adult asthma is known for its female predominance, uncommon remission and unusual mortality. Both childhood and adult asthma have variable presentations, which are described herein. Childhood asthma severity is associated with duration of asthma symptoms, medication use, lung function, low socioeconomic status, racial/ethnic minorities and a neutrophilic phenotype. Adult asthma severity is associated with IgE, FeNO, eosinophilia, obesity, smoking, and low socioeconomic status. Adult onset disease is associated with more respiratory symptoms and asthma medication use despite higher prebronchodilator FEV1/FVC. There is less quiescent disease in adult onset asthma and it appears to be less stable than childhood-onset disease with more relapses and less remissions.